Correlation between Depression, Anxiety, and Stress Levels with Spirituality Levels in Clients at the Narcotics Rehabilitation Centre Baddoka Makassar - Bahtiar Bahtiar; Nur Rakhmi Said (Jurnal Kesehatan Pasak Bumi Kalimantan, 2023)
Clients undergoing drug rehabilitation are susceptible to mental health problems. However, this problem is not explored further in support of the assessment and treatment of clients, especially regarding depression, anxiety, and stress-related aspects of spirituality. The purpose of the study was to determine the relationship between levels of depression, anxiety, and stress with the level of spirituality in clients at the Baddoka BNN Rehabilitation Center. This research uses descriptive quantitative research with a cross-sectional study method. The total sample that participated in this study was 62 clients who underwent rehabilitation as much as the sample was taken using the purposive sampling technique. The instruments used are DASS 21 (The Depression, Anxiety and Stress Scale) to measure the level of depression, anxiety, and stress and DSES (Daily Spiritual Experience Scale) to measure the level of spirituality. The data analysis technique uses Chi Square test analysis. The results of the study obtained that there was no significant relationship between the level of depression and anxiety with the level of spirituality. However, the other results show that there was a significant relationship between stress levels and spirituality levels. The results of this study can be used as a basis for developing assessments, screening, and developing psycho-spiritual-based service interventions for counselors and service providers for clients in rehabilitation centers and other drug rehabilitation services.